Development of biobased socks from sustainable polymer and statistical modeling of their thermo-physiological properties. (1st October 2018) - Maqsood, Muhammad; Seide, Gunnar
Abstract: Polylactic acid (PLA) is a biodegradable and compostable polymer obtained from annually renewable resources and is acknowledged to be sustainable and eco-friendly polymer with substantial commercial prospective as a textile fiber however, this polymer has not been investigated much in apparel applications. Therefore in this study it was aimed to develop biobased compostable socks from PLA draw textured melt spun yarns and to examine the effect of yarn linear density, fabric structure and stitch density on thermo-physiological characteristics of PLA based socks. 100% PLA based multifilament yarns of two different linear densities were melt spun and later draw textured on false twist texturing machine to be used for socks knitting. Single jersey and rib structures were produced with two different stitch densities to investigate their effect on thermal resistance, relative water vapour permeability, thermal conductivity, vertical wicking and air permeability of the socks. Minitab statistical software was employed to analyze the results of test samples. The coefficients of determinations (R 2 values) presented good estimation capability of the established regression models. The outcomes of this research may be useful in determining suitable manufacturing requirements of PLA based socks to accomplish precise thermo-physiological properties. Highlights: PLA fiber has emerged as an eco-friendly alternative to conventional PET fiber. Biobased socks were developed from sustainable polymer. PLA polymer was melt spun and later draw textured to be used for socks knitting. Thermo-physiological properties of the produced socks were investigated. Regression models were developed to predict comfort properties of socks.